Determinant of Financial Performance in Indonesia Firm - Dicky Adiansyah; Rina Yuniarti; Ahmad Junaidi (SENTRALISASI, 2026)
Global climate change and the transition toward green energy have created significant challenges for Indonesia’s manufacturing industry. This study aims to explain the causal relationship between the independent variables ESG and Risk Management Disclosure and the dependent variable, financial performance, with green innovation serving as a moderating variable. The research is grounded in stakeholder theory and contingency theory and employs a quantitative research design.The population of this study consists of all manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sample includes manufacturing firms that meet the research criteria; from a total of 232 companies, 24 firms were selected, resulting in 120 observational units over a five-year period.The findings confirm that ESG, Risk Management Disclosure, and green innovation significantly improve financial performance.These results provide new insights into the integration of green innovation as a moderating factor within the manufacturing sector.